Biography Writing and Authorial Self-Reflection - Štaif , Jiří (Dějiny – teorie – kritika, 2015)
Despite all the various postmodernist trends in historiography, biographies continue to be an essential part of historical literature. And while at the end of the 20th century biography as a genre may have seemed exhausted and dead, the first decades of the new millennium had clearly demonstrated that this is not the case. This holds for both medieval studies and Modern history. Especially in medieval studies, we have recently witnessed almost a rebirth of biographic writing, and that despite the fact that sources for biographies of medieval persons are few and far between and, with but a handful of exceptions, one cannot produce a well-balanced biography where the person of interest would figure as more than just a mute participant of historical events. Czech historians still tend to focus on individuals who were active in politics or culture and using their stories try to capture the outline of the times in which they lived and which they helped mould by their actions. Surprisingly much attention is currently paid to biographies of Czech and Czechoslovak historians of the 19th and 20th centuries. They are seen as one of the ways in which historiographers can come to terms with their own past. And this continuing interest is the focus of our discussion board. Lenka Řezníková in her contribution analyses the causes of increase in biographical writing in the late 18th and the 19th centuries. She focuses on the textual practice of biographies and on the social interaction between ideas about the character, status, and meaning of life of an individual, which contributed to the creation of a modern notion of an individual. Her basic claim is that the quantitative increase in the number of biographies and autobiographies was the result of social changes which in the late 18th century led to the establishment of a new concept of an autonomous subject. Lukáš Fasora analyses the biographical approach to the history of working classes in the German and Anglo-Saxon historiography of recent decades and confronts it with Czech biographical contributions to this subject. And finally, Jiří Štaif uses his experience from writing the social and political biography of František Palacký to consider the various approaches to writing a biography, the limitations of such an enterprise, and its advantages over a narrative discourse.